Control of gradient activation energy on the formation and properties of multiferroic composite thin films. Issue 10 (19th February 2016) - Tang, Yu; Zhang, Yi; Wang, Zongrong; Ma, Ning; Du, Piyi
Abstract : Gradient activation energy, caused by stress from the substrate, makes the crystallinity and properties of multiferroic composite thin films be different at each horizontal micro-layer and change continuously along the normal direction. Abstract : Revealing the control of the formation and properties of multiferroic composite thin film is of great importance in fabricating multiferroic thin films with high performance and facilitating miniaturization and multi-functionalization of devices. In this work, BTO–NZFO nanocomposite thin films were synthesized on ITO-coated glass and quartz substrates by RF magnetron sputtering at sintering temperatures of 600–800 °C. The formation of composite thin films was investigated by means of XRD, SEM and XPS, and the thermodynamic calculation of activation energies of constituent phases was performed. The results show that, controlled by the stress from substrate and gradient activation energies, the crystallinities of the BTO and NZFO phases change continuously along the normal direction of the thin films, and increase with increasing distance from substrate. Below 30 nm, the composite thin films are mostly composed of amorphous phase without detectable grains, due to the too high activation energies of the constituent phases. Above 90 and 120 nm, respectively, the formation of BTO and NZFO crystalline phases in the composite thin films is free of any influence from the substrate and independent of the distance from the substrate, resulting from the small and stable activation energies. The measured permittivity and permeability values of the BTO–NZFO composite thin films, which are average values of all micro-layers with different crystallinities, are directly/strongly controlled by the continuously changeable activation energy along the normal direction of the thin film. Both values are high when the film is thick, and low when the film is thin.